Respuesta :

Answer:

-6x⁷ + 12x − 3

Step-by-step explanation:

Method 1 :

[tex]-3x^0\ (2x^7-4x+1)[/tex]

[tex]= (-3x^0)\times 2x^7-(-3x^0)\times4x+(-3x^0)\times1[/tex]

[tex]= (-3x^0)\times 2x^7+(3x^0)\times4x+(-3x^0)\times1[/tex]

[tex]=-6x^{0+7}+12x^{0+1}-3x^0[/tex]

[tex]=-6x^{7}+12x^{1}-3x^0[/tex]

[tex]=-6x^{7}+12x-3[/tex]

Method 2 :

Note : x⁰ = 1

[tex]-3x^0\ (2x^7-4x+1)[/tex]

[tex]=-3\ (2x^7-4x+1)[/tex]

[tex]=-3\times2x^7-(-3)\times4x+(-3)\times1[/tex]

[tex]=-6x^7+12x-3[/tex]

ACCESS MORE